An ARFID case report combining family-based treatment with the unified protocol for Transdiagnostic treatment of emotional disorders in children - Sarah Eckhardt; Carolyn Martell; Kristina Duncombe Lowe; Daniel Le Grange; Jill Ehrenreich-May (Journal of Eating Disorders, 2019)
Abstract Background This case report discusses the presentation and treatment of a nine-year-old female with a history of significant weight loss and food refusal using a combined approach of Family-Based Treatment (FBT) and the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders in Children (UP-C). Case presentation The patient was diagnosed with avoidant/restrictive food intake disorder (ARFID), separation anxiety disorder, and a specific phobia of choking, and subsequently treated with a modified version of FBT, in conjunction with the UP-C. At the end of treatment, improvements were seen in the patient’s weight and willingness to eat a full range of foods. Decreases in anxiety regarding eating/choking, fears of food being contaminated with gluten, and fears of eating while being away from parents were also observed. Conclusions These findings highlight promising results from this combined treatment approach, referred to as FBT + UP for ARFID. Further research is needed to evaluate the use of this treatment in patients presenting with a variety of ARFID symptoms.